2020
DOI: 10.1002/pits.22439
|View full text |Cite
|
Sign up to set email alerts
|

How does future focus promote study engagement? A moderated mediation model of self‐esteem and dispositional awe

Abstract: Sufficient engagement in studying promotes students' academic performance and ability to compete in the job market. In this study, we explore the role of future focus and dispositional awe in stimulating college students' study engagement. To examine our hypotheses, we conducted a questionnaire survey with 237 students from a national college in China. The results indicate that future focus is positively related to study engagement and that self-esteem mediates this relationship. Moreover, the mediating effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
(106 reference statements)
2
4
0
Order By: Relevance
“…Nevertheless, students higher in FTP still reported higher investment in learning (without taking anxiety into account), which was evident by the positive relationship between FTP and investment in learning. This corroborates previous research that has suggested a motivational role for FTP in education (Andre et al, 2018(Andre et al, , 2019Husman & Shell, 2008;Peetsma et al, 2017;Schuitema et al, 2014;Zhang et al, 2021).…”
Section: Ftp As a Moderator In The Anxiety And Investment In Learning...supporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, students higher in FTP still reported higher investment in learning (without taking anxiety into account), which was evident by the positive relationship between FTP and investment in learning. This corroborates previous research that has suggested a motivational role for FTP in education (Andre et al, 2018(Andre et al, , 2019Husman & Shell, 2008;Peetsma et al, 2017;Schuitema et al, 2014;Zhang et al, 2021).…”
Section: Ftp As a Moderator In The Anxiety And Investment In Learning...supporting
confidence: 92%
“…In our study, we focused on the FTP related to school and professional career because we were interested in exploring the relationship between anxiety and investment in learning in the academic domain. FTP was found to be positively related to various educational outcomes such as learning effort, engagement, achievement, and performance (Andre et al, 2018;Schuitema et al, 2014;Zhang et al, 2021). Particularly, studies have found that FTP in school and professional career positively related to secondary school students' investment in learning.…”
Section: Ftp As a Moderator In The Anxiety And Investment In Learning...mentioning
confidence: 99%
“…The way students handle the numerous challenges encountered within their academic setting sustains their ability to manage the professional challenges that lie ahead [31]. Hence, academic engagement is important for students' achievement, besides following the development of the necessary skills to effectively prepare for the future.…”
Section: Academic Engagementmentioning
confidence: 99%
“…Study engagement refers to the positive and fulfilling experience associated with learning, including energy, focus, and absorption in education (Zhang et al, 2021) high quality of mental energy in the learning process. Concentration refers to the ability to identify with learning and sustain a commitment to it.…”
Section: The Influence Of Students' Self-efficacy On Study Engagementmentioning
confidence: 99%
“…Study engagement refers to the positive and fulfilling experience associated with learning, including energy, focus, and absorption in education ( Zhang et al, 2021 ). Energy reflects a high quality of mental energy in the learning process.…”
Section: Hypotheses Developmentmentioning
confidence: 99%